A comparative study of ethylene and propylene polymerization over titanium–magnesium catalysts of different composition. Issue 16 (19th March 2014) - Nikolaeva, Marina; Matsko, Mikhail; Mikenas, Tatiana; Zakharov, Vladimir
ABSTRACT New data on the molecular weight characteristics of polypropylene (PP) and polyethylene (PE) were obtained from the polymerization over supported titanium–magnesium catalysts differing in their compositions (presence and absence of internal and external donors). Internal and external donors were found to affect the molecular weight of polymers in a different manner for ethylene and propylene polymerization. The introduction of the internal donor increases the molecular weight of PP and does not affect the molecular weight of PE. The effect of external donor introduced to catalytic system on the polymer molecular weight depends on catalyst composition: for a catalyst without internal donor, the introduction of the external donor increases the molecular weight of PP and does not affect that of PE. In the case of catalyst with the internal donor, the introduction of the external donor increases the molecular weight of PP and substantially decreases that of PE. The data on polymerization degree of the polymers produced under conditions when chain transfer with hydrogen was the dominant reaction were used to calculate the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh6c414hb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ktr H/kp</alternatives> values for ethylene polymerization over the catalysts of different composition. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40658.